Iron affinity gel and gallium immobilized metal affinity chromatographic technique for phosphopeptide enrichment: a comparative study - Sagarika Biswas; Ashish Sarkar; Richa Misra (Biotechnology & Biotechnological Equipment, 2017)
Protein phosphorylation is central to most cellular processes. Despite the importance and widespread occurrence of this modification, phosphoproteome analysis of complex biological samples still remains a challenge. The present study has been undertaken to compare iron affinity immobilized metal ion affinity chromatography (Phos-Select™ IMAC) and Gallium immobilized metal ion affinity chromatography (Ga-IMAC) to enrich and characterize phosphopeptides from the whole-cell lysate of Jurkat cells. Our results indicated that enrichment was dependent on the isoelectric point (pI) and molecular mass of the proteins and it was found to be better in case of PHOS-Select IMAC (51.2%) as compared to Ga-IMAC (28.8%). This study compared and analysed phosphopeptide profile of Jurkat cells by two different IMAC techniques and provides advancement in phosphopeptide enrichment methods.